Effect of PFA on strength and water absorption of mortar - Gingos, G.S; Mohamed Sutan, N. (UNIMAS Publisher, 2011)
Partial replacement of cement by mineral admixtures or pozzolans can possibly improve the durability of mortar which directly related to its water absorption. Pulverized Fuel Ash (PFA) is one of the pozzolans that is locally available.